2021
DOI: 10.3390/nu13103377
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Almonds on Gut Microbiota, Glycometabolism, and Inflammatory Markers in Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis of Randomised Controlled Trials

Abstract: The use of nutritional interventions for managing diabetes is one of the effective strategies aimed at reducing the global prevalence of the condition, which is on the rise. Almonds are the most consumed tree nut and they are known to be rich sources of protein, monounsaturated fatty acids, essential minerals, and dietary fibre. Therefore, the aim of this review was to evaluate the effects of almonds on gut microbiota, glycometabolism, and inflammatory parameters in patients with type 2 diabetes. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…A previous study has also shown that an almond-based low carbohydrate diet may improve glucose metabolism in patients with T2DM by increasing SCFA-producing bacteria, including Roseburia, Ruminococcus and Eubacterium, to elevate SCFA production and activate GPR43 to sustain GLP-1 secretion (48). Consistently, another study has suggested that almondbased diets may promote SCFA-producing bacteria while decreasing hemoglobin and body mass index (BMI) in T2DM individuals (241). The Green-Mediterranean diet with a gradual increase in plant components induces specific alterations in the intestinal flora and BCAA metabolism, including an elevation in Prevotella abundance and BCAA degradation as well as a decrease in Bifidobacterium abundance and BCAA biosynthesis, leading to increased insulin sensitivity (242).…”
Section: Diet and Exercisementioning
confidence: 90%
“…A previous study has also shown that an almond-based low carbohydrate diet may improve glucose metabolism in patients with T2DM by increasing SCFA-producing bacteria, including Roseburia, Ruminococcus and Eubacterium, to elevate SCFA production and activate GPR43 to sustain GLP-1 secretion (48). Consistently, another study has suggested that almondbased diets may promote SCFA-producing bacteria while decreasing hemoglobin and body mass index (BMI) in T2DM individuals (241). The Green-Mediterranean diet with a gradual increase in plant components induces specific alterations in the intestinal flora and BCAA metabolism, including an elevation in Prevotella abundance and BCAA degradation as well as a decrease in Bifidobacterium abundance and BCAA biosynthesis, leading to increased insulin sensitivity (242).…”
Section: Diet and Exercisementioning
confidence: 90%
“…Almond (poly)phenolics possess anti-inflammatory, vasodilatory and antioxidant activities ( 15 19 ). Four-weeks intake of almonds has been linked to reduced oxidized LDL and fatty acid peroxidation malondialdehyde (MDA) and creatinine-adjusted urinary isoprostane output ( 17 , 18 ). Limited data suggest reduced levels of depression with increased almond intake that may in part be due to almond-related anti-inflammatory and antioxidant effects ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Between 2020 and 2022 (present day), several other SRMAs of RCTs have been conducted assessing the effect of a specific nut type on markers of glycemic control in people with T2D. Two SRMA’s assessed the effect of almond intake; the first SRMA (8 RCTs) showed a significant lowering in HbA1c but no impact on fasting glucose, insulin, or HOMA-IR [ 36 ], whereas the second SRMA (9 RCTs) showed no impact on markers of glycemic control, including HbA1c, fasting glucose, and insulin [ 37 ]. Another SRMA assessed the effect of pistachio intake in individuals with T2D, prediabetes, and metabolic syndrome (6 RCTs), which showed a significant lowering in fasting glucose and HOMA-IR, but not HbA1c or fasting insulin [ 34 ].…”
Section: Nuts and Diabetes Managementmentioning
confidence: 99%